Las ordenaciones de la universidad de Barcelona de 1638 - Ramis Barceló, Rafael (Historia de las Universidades, 2019)
In this book, the Regulations of the University of Barcelona of 1638 (which had been unpublished) are studied. This was the most important and lasting regulation of the Studium Generale of Barcelona, which had a wide influence on the Catalan Universities during the Baroque Period. Rafael Ramis-Barceló and Pedro Ramis-Serra reproduce the original text in Catalan, and offer an annotated translation into Spanish, preceded by a Preliminary Study.---En este libro se estudian las Ordenaciones de la Universidad de Barcelona de 1638, que habían quedado inéditas. Se trata de la normativa más importante y duradera del Estudio General de Barcelona, que tuvo una amplia influencia en las universidades catalanas del Barroco. Rafael Ramis Barceló y Pedro Ramis Serra reproducen el texto original en catalán, y ofrecen una traducción anotada al castellano, precedida por un estudio preliminar.